Evaluating a work/study programme for Nurses and Midwives at Aga Khan University, Uganda - Hellen Kyakuwaire; Agnes Kirikumwino; Juliet Nabossa; Grace Ann Edwards (University of Johannesburg, 2020)
The work/study programme for nurses and midwives at Aga Khan University School of Nursing and Midwifery (AKU-SONAM) is a unique concept in East Africa. This study explored whether nursing and midwifery students undergoing a work-study programme at AKU-SONAM felt their education was underpinned by an adult education philosophy. A semi-structured questionnaire designed specifically for this study based on the Knowles' (1980) 'Principles of Adult Education' was administered to 96 students who completed their programmes in 2017 and 2018 respectively. Our paper reports on both the positive aspects of students' experiences in this work-study programme, including the improvement of critical thinking skills and the direct transfer of classroom learning to clinical practice, along with negative impacts related to a poor work/life balance. Despite challenges related to quality and delivery highlighted in studies involving nursing and midwifery education in Africa, the findings of our study seem to show a positive experience in addressing the needs of the majority of the participants, as well as in meeting the objectives of the programme. We conclude that understanding the benefits and challenges faced by students will help to ensure the appropriate teaching and learning approaches. Keywords: Work/study programme, Uganda, Nurses and midwives evaluation, Upskilling, Nursing and midwifery education How to cite this article: Kyakuwaire, H., Kirikumwino, A., Nabossa, J. & Edwards, G.A. 2020. Evaluating a work/study programme for Nurses and Midwives at Aga Khan University, Uganda. Scholarship of Teaching and Learning in the South. 4(2): 63-79. https://doi.org/10.36615/sotls.v4i2.129. This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/